The Happiness of the Older Individuals in Indonesia and Its Associated Factors - Dede Dwipayana, I Kadek; Ayu Padini, Putu Rima (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2024)
Indonesia has entered the ageing population phase, marked by the percentage of older individuals exceeding 10 per cent and continuing to rise. Older individuals are more vulnerable to various factors, such as economic non-productivity, declining health conditions, and the need for companionship. Happiness among older individuals is important because productive, healthy, and happy older individuals may become a second demographic dividend for the country’s development. By utilising the Happiness Index Survey (SPTK) 2021 data, this study aims to measure the happiness of Indonesian older individuals and identify the sociodemographic, socioeconomic, health, and social engagement factors associated with it. The happiness index for older individuals in Indonesia is estimated to be at 70.54 points, with 49.3 per cent of them having a happiness index above this number, categorised as happy, and 50.7 per cent falling into the less happy category. Binary logistic regression identifies significant factors associated with happiness among older individuals. These include marital status, education level, type of residence, household income, employment status, ownership of old-age security, non-presence of chronic diseases and disabilities, and frequency of communicating with family. Gender is not significantly associated with happiness among older individuals. Various interventions from stakeholders are crucial to enhance the happiness of older individuals, primarily to protect them from vulnerabilities. These include health protection, empowerment, welfare assurance, and social support for older individuals with limited social relationships.